2014
DOI: 10.1155/2014/797824
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Hesperetin and Naringenin against Apoptosis in Ischemia/Reperfusion-Induced Retinal Injury in Rats

Abstract: Purpose. Hesperetin and naringenin are naturally common flavonoids reported to have antioxidative effects. This study was performed to investigate whether either hesperetin or naringenin has a protective effect against apoptosis on retinal ischemia/reperfusion (I/R) injury. Methods. Retinal I/R was induced by increasing the intraocular pressure to 150 mmHg for 60 minutes. Thirty-three male Wistar albino rats were randomised into 5 groups named control, I/R + sham, I/R + solvent (DMSO), I/R + hesperetin, and I/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 38 publications
0
28
0
1
Order By: Relevance
“…Naringenin (4,5,7-trihydroxy-flavanone) and hesperetin (3,5,7-trihydroxy-4 -methoxyflavanone) ( Figure 5) are the representative flavanones that are found in glycoside form in nature; that form favors their intestinal absorption. They are present in citrus fruits, tomatoes and cherries [211], but unfortunately have limited solubility in water. Kanaze et al reports that oral administration of naringenin results in a low bioavailability (5.81%) in human subjects [212].…”
Section: Flavanonesmentioning
confidence: 99%
“…Naringenin (4,5,7-trihydroxy-flavanone) and hesperetin (3,5,7-trihydroxy-4 -methoxyflavanone) ( Figure 5) are the representative flavanones that are found in glycoside form in nature; that form favors their intestinal absorption. They are present in citrus fruits, tomatoes and cherries [211], but unfortunately have limited solubility in water. Kanaze et al reports that oral administration of naringenin results in a low bioavailability (5.81%) in human subjects [212].…”
Section: Flavanonesmentioning
confidence: 99%
“…Specifically, naringenin has been shown to be neuroprotective in a retinal model of ischaemia‐reperfusion injury. In this study, naringenin was shown to reduce the amount of caspase‐3 positive cells and thus attenuated apoptotic cell death . In another study investigating the effects of naringenin as well as other 5‐hydroxy‐substituted derivatives on a model of myocardial ischaemia‐reperfusion, the data showed naringenin reduced ischaemic injury and restored contractile function, while other derivatives were ineffective .…”
Section: Introductionmentioning
confidence: 60%
“…Neuroprotective effect of naringenin was studied against carbaryl toxicity in mouse neuroblastoma cell line; where it found to be effective neuroprotective by maintenance of mitochondrial membrane potential (54) Chronic treatment of diabetic rats with naringenin prevented abnormal changes in vascular reactivity in diabetic rats through nitric oxide (55) . Therapeutic potential of naringenin was studied in retinopathy where it is proven to be effective for the protection of ocular ischemic diseases (56). Naringenin (Fig.14) can prevent the accumulation of plasma lipids and lipoproteins very effectively.…”
Section: Naringeninmentioning
confidence: 99%